2012
DOI: 10.1371/journal.pone.0046261
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Transporters EAAT4 and EAAT5 Are Expressed in Vestibular Hair Cells and Calyx Endings

Abstract: Glutamate is the neurotransmitter released from hair cells. Its clearance from the synaptic cleft can shape neurotransmission and prevent excitotoxicity. This may be particularly important in the inner ear and in other sensory organs where there is a continually high rate of neurotransmitter release. In the case of most cochlear and type II vestibular hair cells, clearance involves the diffusion of glutamate to supporting cells, where it is taken up by EAAT1 (GLAST), a glutamate transporter. A similar mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 45 publications
0
32
1
Order By: Relevance
“…A previous study of EAAT5 expression in mouse vestibular hair cells and calyx endings reported expression of EAAT5 in type I and type II hair cells as well as the calyx inner face (Dalet et al 2012). Using one of the EAAT5 antibodies used in that study, we also observed immunoreactivity in the calyx inner face, but, in contrast to the previous report, labeling of the calyx outer face was observed, and labeling of type II hair cells was not observed.…”
Section: The Nkaα3 Subunit Colocalizes With Glutamate Transporters Ancontrasting
confidence: 93%
See 2 more Smart Citations
“…A previous study of EAAT5 expression in mouse vestibular hair cells and calyx endings reported expression of EAAT5 in type I and type II hair cells as well as the calyx inner face (Dalet et al 2012). Using one of the EAAT5 antibodies used in that study, we also observed immunoreactivity in the calyx inner face, but, in contrast to the previous report, labeling of the calyx outer face was observed, and labeling of type II hair cells was not observed.…”
Section: The Nkaα3 Subunit Colocalizes With Glutamate Transporters Ancontrasting
confidence: 93%
“…Firstly, the envelopment of the type I hair cell by the afferent calyx precludes glutamate uptake by supporting cells and necessitates mechanisms of glutamate clearance localized directly to the type I hair cell and/or calyx terminal. Indeed, recent work provides evidence that the glutamate transporter EAAT5 is expressed in calyx endings (Dalet et al 2012). Like other glutamate transporters, EAAT5 relies at least indirectly on NKAs to generate the ion gradients necessary for the Na + -dependent transport of glutamate (Beart and O'Shea 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2), and because puncta of high ΔpH were observed at locations distant from sites of quantal release (Fig. 4), we can rule out synaptic vesicles as the primary source of cleft acidification (24,25). It is more likely that protons were extruded into the cleft during hair cell depolarization through mechanisms such as Na + /H + exchange or electrogenic Na + /HCO 3 cotransport.…”
Section: Discussionmentioning
confidence: 94%
“…In fact, a handful of proteins necessary for glutamateric signaling that are relatively selectively expressed in the inner ear have been identified. For example, VLUT3, a vesicular glutamate transporter (Seal et al, 2008), otoferlin, a Ca 2+ sensor necessary for glutamate release from hair cells (Roux et al, 2006), and EAAT5, a glutamate transporter expressed in the vestibular sensory epithelia (Dalet et al, 2012) show more or less restricted expression to the inner ear (or ribbon synapses). Therefore, future work should investigate the expression of novel Shank isoforms in the inner ear.…”
Section: Discussionmentioning
confidence: 99%